Kinetics of Anti-Spike SARS-CoV-2 antibodies post Sputnik V homologous-scheme vaccination in health personnel - Jofre, Claudio Francisco (2021)
The occurrence of mutations is a natural and expected event within the evolutionary process of viruses. The massive spread of the SARS-CoV-2 led to the accumulation of mutations within the viral genome, generating new variants. The capacity to monitor the data in real time impacts directly on the COVID-19 pandemic public health response. The knowledge of the community circulation of Variants Of Concern (VOCs), such as , , and , or Variants Of Interest (VOIs), as and , requires sampling and sequencing strategies to ensure representativeness and reliability of the results. In San Luis, the PLSP has access to COVID-19 positive samples and works closely with the Programa de Epidemiología. Our health institution applied two different surveillance strategies to detect the SARS-CoV-2 variants. The first strategy consisted of whole or partial genome sequencing, which were carried out at ANLIS-Malbrán and PAIS Project. On the other hand, a PCR screening strategy was developed by researchers from the UNSL and implemented for the early detection of the VOC. A total of 169 positive samples were analyzed applying the first strategy among epidemiological weeks (EW) 14 to 36 in 2021. 113 samples were selected by regular sampling, taking into account high transmission areas, different age ranges, geographic location and severity. Additionally, 38 immunized people, 7 samples suspected of reinfection and 7 travelers were analyzed. The main variants found were: (43%), (11%), (5%), (1%), and other Not VOC/VOI (27%). Interestingly, since EW 19, the proportion of cases associated with VOC and VOI increased while those associated with VOC decreased. The second strategy was applied on 1367 samples from EW 25 to 40 and VOC was not detected as a circulant variant in San Luis. In this work we show genomic evidence of local transmission of SARS-CoV-2 VOC , and . The variant was only found in one traveler who returned from Colombia. It should be noted that, according to the results obtained in this work, the VOC and VOI are the main circulating variants in the province, while VOC is not detected nowadays. The results were opportunely communicated to the authorities to be used for the benefit of public health.